Prevalence of rheumatoid factor and serum uric acid level in persons above 25 years in Calabar metropolis - Okeke, Humphrey; Usoro, Chinyere; Anyanwu, Augusta (Journal of medical and allied sciences, 2020)
This research was aimed at assessing the prevalence of rheumatoid factor (RF) in people of our locality to aid the inclusion of rheumatoid factor test for the diagnosis of the disease. Specifically, this research sought to: determine and compare the presence of rheumatoid factor in both young and old adults; find out which gender is more affected in our locality, and determine the uric acid levels in both symptomatic and asymptomatic subjects. The presence of rheumatoid factor in the serum of 100 subjects aged above 25 years in Calabar metropolis was determined using a Rheumatoid Factor rapid agglutination test. Six (6) out of eighty-two (82) males and two (2) out of eighteen (18) females were positive for rheumatoid factor, giving a total of eight (8) rheumatoid factor +ve subjects. The mean age, body mass index (BMI) and serum uric acid (SUA) level for rheumatoid factor +ve subjects were 45.13±14.13 years, 26.69±2.23 kg/m2 and 10.02±6.78 mg/dl respectively while the mean age, BMI and SUA level for rheumatoid factor -ve were 37.57±5.76 years, 24.46±3.92 kg/m2, 7.04±3.88 mg/dl respectively. The mean age and serum uric acid level in rheumatoid factor +ve subjects were significantly higher (p<0.05) when compared with rheumatoid factor -ve subjects. The mean BMI for rheumatoid factor +ve subjects was also significantly higher (p<0.05) when compared with rheumatoid factor -ve subjects. This research work shows that the prevalence of rheumatoid factor in this locality, though low, is higher than those studied in other countries. Women are more affected than men with rheumatoid arthritis. There is an increased level of serum uric acid in RF +ve and symptomatic subjects. Therefore, there is a need to introduce rheumatoid factor analysis in the medical laboratories for proper diagnosis and treatment of individuals with rheumatoid arthritis.